2023
DOI: 10.1002/jbt.23368
|View full text |Cite
|
Sign up to set email alerts
|

Eriodictyol regulated ferroptosis, mitochondrial dysfunction, and cell viability via Nrf2/HO‐1/NQO1 signaling pathway in ovarian cancer cells

Abstract: This study aimed to investigate the antitumor effect and the underlying molecular mechanism of eriodictyol on ovarian cancer cells. CaoV3 and A2780 were exposed to eriodictyol at different concentrations of 0−800 μM. Cell apoptosis and viability were determined by TdT-mediated dUTP Nick-End Labeling (TUNEL) assay and Cell Counting Kit-8 (CCK-8) assay, respectively. Mitochondrial membrane potential was evaluated by flow cytometers with a JC-1 detection kit. Fe 2+ content was evaluated using an iron assay kit. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Other studies found that eriodictyol regulated ferroptosis in OC to exert an antitumor effect. Further experiments showed that eriodictyol induced ferroptosis and mitochondrial dysfunction through the Nrf2/HO-1/NQO1 pathway [ 26 ]. SLC7A11 and GPX4 are the most important regulators of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that eriodictyol regulated ferroptosis in OC to exert an antitumor effect. Further experiments showed that eriodictyol induced ferroptosis and mitochondrial dysfunction through the Nrf2/HO-1/NQO1 pathway [ 26 ]. SLC7A11 and GPX4 are the most important regulators of ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, eriodictyol downregulated NRF2 expression in tumor tissues in mice xenograft models. Thus, eriodictyol regulated ferroptosis, ROS levels and cell viability and modulated NRF2 signaling in ovarian cancer [ 66 ]. These data are very important and are in agreement with two important studies [ 67 , 68 ] reporting that SLC7A11 is a prognostic ferroptosis-related gene in ovarian cancer.…”
Section: Slc7a11 Modulation By Natural and Synthetic Compounds In Ova...mentioning
confidence: 99%
“… 543 BC Ketamine Acetylation KAT5 Ketamine induces ferroptosis through inhibiting the expression of GPX4 by attenuating KAT5 on the promoter region of GPX4, repressing the enrichment of histone H3 lysine 27 acetylation (H3K27ac) and RNA polymerase II (RNA pol II) 544 GBM ALZ003 Ubiquitination Androgen receptor ALZ003 induces FBXL2-mediated AR ubiquitination and degradation. ALZ003 significantly inhibited the survival of glioblastomathrough inducing ferroptosis 545 Glioma Paeoniflorin Ubiquitination NEDD4L/STAT3 Paeoniflorin might function as an effective drug for glioma by inducing ferroptosis via upregulation of NEDD4L and mediates the ubiquitination of STAT3 repression of Nrf2, GPX4 546 GBM Myrislignan Phosphorylation NF-κB Myrislignan inhibited the activation of NF-κB signaling by blocking the phosphorylation of p65 protein and induced ferroptosis through the Slug-SLC7A11 signaling pathway in GBM cells 547 OC Eriodictyol Phosphorylation Nrf2 Eriodictyol induces ferroptosis through downregulating Nrf2 phosphorylation,thereby decreasing protein levels of SLC7A11 and GPX4 550 Thyroid cancers RSL3 Phosphorylation mTOR RSL3 activate ferroptosis through suppressing mTOR signaling pathway triggered autophagy. GPX4 genetic knockdown mirrored RSL3 effect on mTOR pathway suppression.…”
Section: Modulation Of Epigenetic and Posttranslational Modifications...mentioning
confidence: 99%
“…Eriodictyol induces ferroptosis by downregulating Nrf2 phosphorylation, thereby decreasing the protein levels of SLC7A11 and GPX4 in ovarian cancer. 550 …”
Section: Modulation Of Epigenetic and Posttranslational Modifications...mentioning
confidence: 99%